Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd004446.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Emergency ultrasound-based algorithms for diagnosing blunt abdominal trauma

Abstract: There is insufficient evidence from RCTs to justify promotion of ultrasound-based clinical pathways in diagnosing patients with suspected blunt abdominal trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 28 publications
0
35
0
1
Order By: Relevance
“…17,25,3335,41,49 While we did not review studies of clinical outcomes, a Cochrane systematic review found that ultrasound-based patient management algorithms reduced CT ordering by 50%. 57 …”
Section: Limitationsmentioning
confidence: 99%
“…17,25,3335,41,49 While we did not review studies of clinical outcomes, a Cochrane systematic review found that ultrasound-based patient management algorithms reduced CT ordering by 50%. 57 …”
Section: Limitationsmentioning
confidence: 99%
“…the focused assessment with sonography in trauma [FAST] examination in blunt abdominal trauma). 14 Kim et al 15 question the 'uncritical acceptance' of the diagnostic role of POCUS, which they believe is 'spurred by enthusiasm, not science'.…”
Section: Introductionmentioning
confidence: 99%
“…However, the importance of this technology in early trauma management remains controversial. Besides its cost and the risk of radiation exposure, whole-body CT raises safety concerns about time delays due to patient transportation from the emergency room to the CT room and scanning [1-3]. …”
Section: Introductionmentioning
confidence: 99%